2005
DOI: 10.1002/pssc.200460773
|View full text |Cite
|
Sign up to set email alerts
|

Hopping photoconductivity and its long‐time relaxation in two‐dimensional array of Ge/Si quantum dots

Abstract: Photoconductivity excitation kinetics has been studied in a two-dimensional array of Ge/Si quantum dots under illumination with different light wavelength. Both negative and positive photoeffects depending on dot occupations with holes were observed. Long-time conductivity dynamics (typically, 10 2 -10 4 sec at T=4.2 K) has been revealed as well as after switch on and switch off the illumination, displaying a sluggish temporal dependence. The observed effects were not suppressed by decreasing of the excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, a number of issues have remained only partly covered, and some aspects have not even been significantly addressed. For example, the number of studies devoted to internal photoelectrical effect and, in general, photophysics of low-dimensional structures (especially the relaxation phenomena governing the nonequilibrium charge carriers’ recombination) seems to be much smaller. The last statement is particularly valid when one deals with 3D assemblies of semiconductor QDs. Actually, problems related to equilibrium and nonequilibrium conductivity of 3D nanoparticle assemblies and also of nanocrystalline films have been studied to a much lesser extent. ,,, , Perhaps the most notable among these, at least in relation to our present study, are the studies of photophysical phenomena in nanostructured CdSe, , ,,, nanostructured silicon, ,,,, nanocrystalline GaN, as well as thin films of silicon nanocrystals, InP nanoparticle arrays, nanostructured InAs/GaAs, and PbSe nanocrystal arrays …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of issues have remained only partly covered, and some aspects have not even been significantly addressed. For example, the number of studies devoted to internal photoelectrical effect and, in general, photophysics of low-dimensional structures (especially the relaxation phenomena governing the nonequilibrium charge carriers’ recombination) seems to be much smaller. The last statement is particularly valid when one deals with 3D assemblies of semiconductor QDs. Actually, problems related to equilibrium and nonequilibrium conductivity of 3D nanoparticle assemblies and also of nanocrystalline films have been studied to a much lesser extent. ,,, , Perhaps the most notable among these, at least in relation to our present study, are the studies of photophysical phenomena in nanostructured CdSe, , ,,, nanostructured silicon, ,,,, nanocrystalline GaN, as well as thin films of silicon nanocrystals, InP nanoparticle arrays, nanostructured InAs/GaAs, and PbSe nanocrystal arrays …”
Section: Introductionmentioning
confidence: 99%
“…Actually, problems related to equilibrium and nonequilibrium conductivity of 3D nanoparticle assemblies and also of nanocrystalline films have been studied to a much lesser extent. 20,21,28,[30][31][32][33][35][36][37][38][39][40][41][42][43][44][45] Perhaps the most notable among these, at least in relation to our present study, are the studies of photophysical phenomena in nanostructured CdSe, [17][18][19][20][21][37][38][39][40]42,44,45 nanostructured silicon, 22,28,35,41,43 nanocrystalline GaN, 26 as well as thin films of silicon nanocrystals, 28 InP nanoparticle arrays, 29 nanostructured InAs/ GaAs, 36 and PbSe nanocrystal arrays. 30 Actually, the formations, built up by close packing of individual QDs (such as, e.g., the 3D assemblies of QDs), are in the very focus of contemporary physical chemistry due to the number of very significant and still only partly explained aspects related to collective physical phenomena which develop upon interaction of the proximal QDs constituting the 3D QD assemblies, while keeping certain individual characteristics of QDs.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the barrier height lowers and the barrier width narrows under light irradiations owing to enhanced quantum confinements in CdS which resulted from Au nanosheets. The original investigations of quantum confinement effect indicated that the long time illumination decreases the barrier height resulting in more effective holes captures and larger relaxation rate [23]. In addition, the barrier lowering upon light excitations can also be assigned to Fermi level shift towards the intrinsic Fermi level [24].…”
Section: Resultsmentioning
confidence: 99%